The Kombi trail : across three continents in a VW van - Cox, Robert (I.B. Tauris, 2013)
Cambridge, 1961. A group of students set off on the trip of a lifetime. Against the backdrop of the Cold War they travel through the Soviet Union to the Middle East, South Asia and on to Africa. Their mode of transport? The iconic VW Kombi. This book tells the story of that trip, not just the people they met and the places they saw, but the many experiences - sometimes nerve-wracking, sometimes bizarre - that they encountered along the way. It provides a fascinating insight into a world on the brink of change - seen through the eyes of nine young men fresh from university. The two VW Kombis do.